Strengths of Taiwan’s Medical Device Industry (International Journal of Automation and Smart Technology, 2012)
This paper presents an overview of the medical device manufacturing industry in Taiwan.  Taiwan’s medical device manufacturers have achieved mature production technology in homecare products. With assistance provided to international giants through Original Equipment Manufacturer and through sales of self-owned brands, they are securing a predominant position on the global market. Contact lenses and glucose meters made in Taiwan have also shown significant growth in production and exports for the past few years and have become potential export-oriented medical devices for Taiwan. Taiwan’s manufacturers can quite professionally deal with issues such as flexible manufacturing and process cost management, and they are rather competitive in emerging markets that demand high quality and fair prices. These qualities help maintain the continuous increase in export momentum. In addition, international manufacturers, one after the other, are establishing their research and development centers in China and purchasing related parts and components locally to form their supply chains in Asia. This helps Taiwan’s manufacturers in other industrial sectors who are proactively making investments in the medical device industry and driving high value for the industry get the upper hand when they seek to connect with the global medical device industry, as well as be able to cut into the international medical device supply chain in the future.